2020
DOI: 10.3389/fpls.2020.00777
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Sulfenylated Cysteines in Arabidopsis thaliana Proteins Using a Disulfide-Linked Peptide Reporter

Abstract: In proteins, hydrogen peroxide (H 2 O 2) reacts with redox-sensitive cysteines to form cysteine sulfenic acid, also known as S-sulfenylation. These cysteine oxidation events can steer diverse cellular processes by altering protein interactions, trafficking, conformation, and function. Previously, we had identified S-sulfenylated proteins by using a tagged proteinaceous probe based on the yeast AP-1-like (Yap1) transcription factor that specifically reacts with sulfenic acids and traps them through a mixed disu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 55 publications
1
31
0
Order By: Relevance
“…There is a lot of evidence that there is an overlap between ROS and H 2 S; therefore, together, protein cysteine oxidation and persulfidation may represent a mechanism for the modulation of signaling processes induced by developmental or environmental stress events. In recent years, many proteins have been described as sulfenylation targets in Arabidopsis in several works, revealing >2000 targets for this modification ( De Smet et al , 2019 ; Huang et al , 2019 ; Wei et al , 2020 ). In a comparison performed between the sulfenylated and the previously identified persulfidated proteins, >6000 targets ( Aroca et al , 2015 , 2017 a ; Laureano-Marín et al ., 2020 ; Jurado-Flores et al , 2021 ) revealed that 82% of the sulfenylated proteome described in Arabidopsis also undergo persulfidation ( Fig.…”
Section: Hydrogen Sulfide Actionmentioning
confidence: 99%
“…There is a lot of evidence that there is an overlap between ROS and H 2 S; therefore, together, protein cysteine oxidation and persulfidation may represent a mechanism for the modulation of signaling processes induced by developmental or environmental stress events. In recent years, many proteins have been described as sulfenylation targets in Arabidopsis in several works, revealing >2000 targets for this modification ( De Smet et al , 2019 ; Huang et al , 2019 ; Wei et al , 2020 ). In a comparison performed between the sulfenylated and the previously identified persulfidated proteins, >6000 targets ( Aroca et al , 2015 , 2017 a ; Laureano-Marín et al ., 2020 ; Jurado-Flores et al , 2021 ) revealed that 82% of the sulfenylated proteome described in Arabidopsis also undergo persulfidation ( Fig.…”
Section: Hydrogen Sulfide Actionmentioning
confidence: 99%
“…102 As well as this chemical probe, a non-invasive SOHtrapping biosensor, the plant-optimized and affinity-tagged yeast AP-1 (YAP1C), has been exploited to capture and identify sulfenylated proteins in Arabidopsis, including characterisation of the sulfenome at a subcellular level. 103,104 These probes are currently revealing the extent to which overall cysteine oxidation is impacted by ROS stress; it will be interesting to determine whether these modifications initiate specific signalling events, e.g. by modulating the stability of proteins with N-terminal cysteine residues via the Cys/Arg branch of the N-degron pathway.…”
Section: Protein Oxidation Productsmentioning
confidence: 99%
“…GSH also interacts with NO to form S -nitrosoglutathtione (GSNO) which is regarded as a NO reservoir [ 58 ]. S -sulfenylation, which results from the oxidation of the thiol group to Cys sulfenic acid, is mediated by H 2 O 2 [ 59 , 60 ]. S -acylation is a reversible oxiPTM involving the addition of a fatty acid, such as palmitate or stearate, to specific cysteines through thioester bonds [ 61 , 62 ].…”
Section: Protein Persulfidation and Other Cysteine Modificationsmentioning
confidence: 99%